All the way to the top : how one girl's fight for Americans with disabilities changed everything - Pimentel, Annette Bay; Ali, Nabi H.; Keelan, Jennifer, 1981- (Naperville, Illinois : Sourcebooks Explore, 2020)
Jennifer Keelan was determined to make a change--even if she was just a kid. She never thought her wheelchair could slow her down, but the way the world around her was built made it hard to do even simple things. Jennifer knew that everyone deserves a voice! Then the Americans with Disabilities Act, a law that would make public spaces much more accessible to people with disabilities, was proposed to Congress. And to make sure it passed, Jennifer went to the steps of the Capitol building in Washington DC to convince them. And, without her wheelchair, she climbed. All the way to the top!
School Library Journal, February 2020
Publishers Weekly, January 2020
Booklist, February 2020
Kirkus Review, January 2020
Includes bibliographical references.
2.3
Keywords: Keelan, Jennifer, -- 1981- -- Juvenile literature; Children with disabilities -- Biography -- Juvenile literature; People with disabilities -- Legal status, laws, etc -- United States -- Juvenile literature; Human rights workers -- United States -- Biography -- Juvenile literature; Keelan, Jennifer, -- 1981-; Children with disabilities; People with disabilities -- Legal status, laws, etc; Human rights workers; Biographies; Nonfiction picture books